The Relationship of Social Control and Self-Management to Online Game Addiction in Adolescents - Damaris Kakisina; I Ketut Andika Priastana; Dwi Prima Hanis Kusumaningtiyas (PROMOTOR, 2023)
Background: Online game is a very popular game, including among teenagers. Addiction to online games is caused by low self-management, as a result, adolescents put aside their responsibilities, and adolescents in their social life have means in the form of control to regulate behavior so that adolescent behavior has conformist boundaries. Social control is a process that educates the public to comply with prevailing social norms and values. Self-management is an attempt to plan, for the activities carried out by adolescents. The purpose of this study was to identify the relationship between social control and self-management toward online game addiction in adolescents at LKSA Widhya Asih Melaya. Methods: This study used a cross-sectional design. The population in this study were all teenagers who play online games living at LKSA Widhya Asih Melaya. The sample of this research is 53 respondents. This research uses probability sampling with a simple random sampling technique. Data analysis was performed using univariate and bivariate analysis. Results: This study found the results of the analysis of social control on online game addiction in adolescents with a correlation coefficient (r) of 0.709, where r count > r table (0.000) and p-value = 0.000 (p <0.25) and the results of self-analysis management of online game addiction in adolescents correlation coefficient (r) of 0.454, where r count > r table (0.000) and p-value = 0.001 (p <0.25). Conclusion: There is a relationship between social control and self-management towards online game addiction in adolescents at LKSA Widhya Asih Melaya.